Unprotected Carbohydrates as Starting Material in Chemical Synthesis: Not Just a Challenge but an Opportunity - Saloranta, Tiina; Leino, Reko (Synlett, 2015)
Development of reaction sequences that utilize renewable resources, such as carbohydrates, as starting material is of topical interest. Particularly attractive are reaction protocols where unprotected mono- and oligosaccharides are applied. Herein, selected approaches for direct derivatization of unprotected carbohydrates are highlighted. Ultimately, such methodologies are also applicable for natural polysaccharides resulting in rapid development of novel functional biobased materials for future applications.1 Introduction2 Reacting Unprotected Carbohydrates as Aldehydes3 Approaches for Selective Reactions Targeting the Nonanomeric Hydroxyl Groups on Unprotected Carbohydrates4 Protecting-Group-Free Synthesis of Glycoclusters and Glycoconjugates5 Conclusions
Keywords: carbohydrates; chiral pool; chemoselectivity; regioselectivity; green chemistry